2020
DOI: 10.1093/infdis/jiaa581
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibody Avidity Responses in COVID-19 Patients and Convalescent Plasma Donors

Abstract: Background Convalescent plasma therapy is a leading treatment for conferring temporary immunity to COVID-19 susceptible individuals or for use as post-exposure prophylaxis. However, not all recovered patients develop adequate antibody titers for donation and the relationship between avidity and neutralizing titers is currently not well understood. Methods SARS-CoV-2 anti-spike and anti-nucleocapsid IgG titers and avidity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
88
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 30 publications
20
88
1
2
Order By: Relevance
“…This feature correlates with the finding that the humoral immune response is often higher and more stable in patients with severe disease compared to control patients that only developed mild symptoms (11). It is also in line with the findings by Benner et al (33), who reported on a relative increase in avidity of IgG towards SARS CoV-2 in hospitalized patients.…”
Section: Determination Of Avidity Revealed Quite Low Values Of Aviditsupporting
confidence: 93%
See 2 more Smart Citations
“…This feature correlates with the finding that the humoral immune response is often higher and more stable in patients with severe disease compared to control patients that only developed mild symptoms (11). It is also in line with the findings by Benner et al (33), who reported on a relative increase in avidity of IgG towards SARS CoV-2 in hospitalized patients.…”
Section: Determination Of Avidity Revealed Quite Low Values Of Aviditsupporting
confidence: 93%
“…These data confirm that the immune response towards SARS CoV-2 proteins shows an initial rise in avidity, reaching varying low to intermediate values, followed by cessation of further continuation of avidity maturation. A general low avidity of IgG towards SARS CoV-2 proteins has also been reported by other groups (13,14,33,34) though these authors did not recognize the specific kinetics of avidity maturation with its initial onset, followed by abrogation of maturation. Figure 3 illustrates the abrogation of avidity maturation in a characteristic case.…”
Section: Determination Of Avidity Revealed Quite Low Values Of Aviditmentioning
confidence: 59%
See 1 more Smart Citation
“…Although our study has limited data on temporal dynamics (< 45 days) to correlates SARS-CoV-2 antibody avidity with the illness severity, it was observed that the majority of patients who had symptoms showed low avidity. Our data is by what was reported to SARS-CoV-2 infection with low IgG antibody avidity during the 50 days after symptoms onset 42 , however, evaluating antibodies against nucleoprotein 55 , and to SARS-CoV-2 anti-spike and antinucleoprotein, that reached the avidity peak at 21 after days of symptoms onset, during a study period median of 45days 42 .…”
Section: Resultssupporting
confidence: 71%
“…At the same time, IgG2 and IgG4 are less detectable in patients sera 29 , suggesting that IgG subclasses as an important marker to distinguish disease timepoint and, perhaps, disease severity. Other factors can also contribute to the understanding of humoral responses to SARS-CoV-2 and the role of neutralizing antibodies in the convalescent plasma of donors, such as an association between antibody neutralizing titers and antibody avidity 42 . Antibodies produced by patients that recovered from coronavirus disease 2019 (COVID-19) have been used as a "molecular framework" to design antibody-based therapies 43 .…”
Section: Introductionmentioning
confidence: 99%